Basal Cell Adenoma: A rare case report with immunohistochemical analysis (Indian Journal of Case Reports, 2018)
Basal cell adenoma (BCA) of the salivary gland is a rare benign monomorphic adenoma accounting for approximately 1–2% of all salivary gland tumors. It is characterized by the presence of sheets/nests of monomorphic cells with a prominent basement membrane. An absence of myxoid and chondroid stroma separates it from the pleomorphic adenoma. Participation of myoepithelial cells is still a controversial issue in the histogenesis of this tumor. We are presenting a case of BCA of the parotid gland in an elderly male patient. A panel of immunohistochemical markers is used to confirm its benignity and emphasize its use to differentiate it from other common histological entities. We briefly review the literature and discuss the differential diagnosis of this rare entity.